Database Access Management and Monitoring System for Solar and Hydropower - Abdullah, Ag Sauffie; MOHD FADLY BIN ABD RAZAK (Progress in Engineering Application and Technology, 2021)
The main idea of this study is monitoring system for solar and energy power. To observe the solar and hydropower is needing a lot of time without monitoring system. This research main objective is to build a monitoring system to be able to access from anywhere. For conducting this study, Graphical User Interface need to be built for user easy to interact. Create a web base design using PHP and database using influxDB to make the data easy to manage. The data will show the reading of voltage and current obtain from Solar and Hydropower energy. This work provides users with an easy to use Web link for which they can remotely access for monitoring data. The system can be access anywhere and been proof on the result. User only need to sign-up using their email and they can sign-in using information they give on the sign-up page.